EU Horizon 2020 subsidy instruments in Finnish unlisted green high-technology SMEs : utilization, impacts and experiences of grants from the case companies’ perspectives - Kurki, Timo (My University, 2021)
The research and development activities are vital for economic development, although those are not at a socially optimal level. The issue is more severe in novel green high-technology small and medium-sized enterprises, which are resource-constrained and might find investing in their research and development unappealing since it is challenging for green companies to reap the full benefits of their products due to externalities and spillovers. Therefore, the economic environment for these companies could be mitigated by public subsidization. However, subsidization might be controversial as it might not attract or incentivize green SMEs to allocate and invest their own funds in innovation activities and could also lead to deadweight or crowding effects. As pecking order theory addresses the green high-technology SMEs might encounter financial barriers because of insufficient turnover and uncertainty related to their technologies. Moreover, being less-established actors, the green SMEs face legitimacy challenges that can be difficult to overcome. The EU has approached these obstacles and alleviated the underinvestment with its Horizon 2020 framework program that offers funding for innovative projects. As the H2020 funding is granted by a respectable body, the certification could be leveraged by the companies to attract resources and network with consortium or industry partners. The objective of this thesis is to examine Finnish unlisted green high-technology SMEs and the EU’s H2020 framework program. The study pursues to answer for the objectives by addressing the SMEs’ motives to apply for the H2020 subsidies, how the SMEs have utilized the instruments and what type of impacts have been realized. Also, reporting and cooperation in the H2020 program are studied. The empirical part of the thesis was conducted by interviewing 10 case companies in the green sector. The study finds that funds and networking by the H2020 are the primary factors to apply for the subsidies whereas, surprisingly, the EU certification was not important and occasionally recognised as disadvantageous. Moreover, although the H2020 subsidy was leveraged when obtaining external capital, the resource constraints prevented investing additional internal funds. However, the H2020 projects can be quite large in relation to the size of the SMEs and thus, tie up companies’ resources, creating a forced crowding-in effect.

Tutkimus- ja kehitystoiminta ovat talouden kehityksen kannalta elintärkeitä, mutta eivät ole tällä hetkellä sosiaalisesti optimaalisella tasolla. Erityisesti vihreät korkean teknologian pk-yritykset ovat resursseiltaan rajoittuneempia sekä saattavat nähdä investoimisen vähemmän houkuttelevampana, koska niiden on haastavaa saada tuotteistaan täysimääräinen hyöty ulkoisvaikutusten vuoksi. Tästä johtuen, kyseisten yritysten taloudellista toimintaympäristöä voidaan parantaa julkisten tukien avulla. Kuitenkin, tukeminen saattaa olla ristiriitaista, sillä se ei välttämättä houkuttele tai kannusta vihreitä yrityksiä allokoimaan ja investoimaan varojaan innovaatiotoimintoihin ja voi johtaa myös rahoituksen syrjäytymisvaikutuksiin. Kuten rahoituksen nokkimisjärjestyksen teoria esittää, vihreät korkean teknologian pk-yritykset saattavat kohdata rahoituksellisia rajoitteita riittämättömän liikevaihdon tai teknologiaan kohdistuvan epävarmuuden takia. Lisäksi vähemmän vakiintuneina toimijoina vihreät pk-yritykset kohtaavat legitimiteettihaasteita, joita voi olla vaikea ylittää. EU on lähestynyt aihetta ja tukenut ali-investointeja Horisontti 2020 -puiteohjelmalla, joka tarjoaa rahoitusta lupaaville innovatiivisille projekteille. Koska H2020-tukirahoituksen myöntää huomionarvoinen taho antaa sertifiointi yrityksille erinomaisen mahdollisuuden houkutella yritykseen muita resursseja ja verkostoitua konsortioiden sekä toimialan kumppaneiden kanssa. Tämän työn tavoitteena on tutkia suomalaisia listaamattomia vihreitä korkean teknologian pk-yrityksiä ja EU:n H2020 -puiteohjelmaa. Tutkimus pyrkii vastaamaan työn tavoitteisiin käsittelemällä pk-yritysten motiiveja hakea H2020-tukia, kuinka pk-yritykset ovat hyödyntäneet tuki-instrumentteja ja millaisia vaikutuksia tuilla on ollut. Lisäksi tarkastellaan raportointia ja yhteistyötä H2020-puiteohjelmassa. Tutkimuksen empiirinen osa suoritetaan haastattelemalla 10 vihreällä sektorilla operoivaa pk-yritystä. Tutkimuksessa havaitaan, että H2020-ohjelman tarjoamat varat ja verkostoituminen ovat ensisijaisia syitä tukien hakemiseen, kun taas yllättäen EU-sertifikaattia ei koettu arvokkaaksi ja todettiin toisinaan jopa epäsuotuisaksi. Lisäksi, vaikka H2020-tukea hyödynnettiin ulkoisen pääoman hankkimisessa, resurssirajoitukset estivät pääosin yritysten sisäisten lisävarojen vivutuksen. Kuitenkin, H2020-hankkeet voivat olla niin suuria verrattuna pk-yritysten kokoon, että ne sitovat yritysten resursseja hankkeeseen luoden välttämättömän vipuvaikutuksen.
Keywords: H2020, subsidies, SMEs, R&D, green innovation, leverage, certification, crowding effect